Rassushin’s precedent: to save a cultural artifact - Lisitsina, Yana (project baikal, 2021)
Preservation of cultural heritage is a complex task regarded from legislative, professional and sociocultural aspects. It demands a very delicate approach. At the same time, the heritage preservation system in the Russian Federation has a number of problems related to imperfection of the institution of historical and cultural expertise, which allows removing obvious cultural resources from the field of state protection. The civil society can resist such incidents, as evidenced by the case of the Irkutsk architectural and historic monument, Doctor Rassushin’s House (early 20th century).
Keywords: Irkutsk; cultural heritage; architecture; expertise; Doctor Rassushin’s House; M. G. Meerovich